2008
DOI: 10.1128/jvi.00155-08
|View full text |Cite
|
Sign up to set email alerts
|

Subdominant CD8 T-Cell Epitopes Account for Protection against Cytomegalovirus Independent of Immunodomination

Abstract: Cytomegalovirus (CMV) infection continues to be a complication in recipients of hematopoietic stem cell transplantation (HSCT). Preexisting donor immunity is recognized as a favorable prognostic factor for the reconstitution of protective antiviral immunity mediated primarily by CD8 T cells. Furthermore, adoptive transfer of CMV-specific memory CD8 T (CD8-T M ) cells is a therapeuticAllogeneic hematopoietic stem cell transplantation (HSCT) combined with donor lymphocyte infusion is a promising therapeutic opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 64 publications
4
95
0
Order By: Relevance
“…Absence of sensitization by MEF exposed to UV light-inactivated virus showed that viral gene expression is required, thus excluding a possible recognition of virion protein-derived peptides [12,13] as well as of cellular peptides induced by the signaling and the resulting global change of the cellular transcriptome that is associated with the viral entry process (for reviews see [14,15]). In accordance with all what we have learnt about immunoevasins encoded by mCMV (for reviews see [5,10,16,17], as well as the article by Doom and Hill in this issue of MMI), MEF infected with mCMV-WT.BAC stimulated only a minor fraction of the IE1-specific CTL in this T cell line, most likely those with the highest avidity. Absence of viral immunoevasins m04/gp34 and m06/gp48 in MEF infected with the respective deletion mutant mCMVDm04 + 06 improved peptide presentation and thus recruited also CTL with somewhat lower avidity.…”
Section: Nkg2d Expression and Target Cell Recognition By An Ie1-epitomentioning
confidence: 86%
See 1 more Smart Citation
“…Absence of sensitization by MEF exposed to UV light-inactivated virus showed that viral gene expression is required, thus excluding a possible recognition of virion protein-derived peptides [12,13] as well as of cellular peptides induced by the signaling and the resulting global change of the cellular transcriptome that is associated with the viral entry process (for reviews see [14,15]). In accordance with all what we have learnt about immunoevasins encoded by mCMV (for reviews see [5,10,16,17], as well as the article by Doom and Hill in this issue of MMI), MEF infected with mCMV-WT.BAC stimulated only a minor fraction of the IE1-specific CTL in this T cell line, most likely those with the highest avidity. Absence of viral immunoevasins m04/gp34 and m06/gp48 in MEF infected with the respective deletion mutant mCMVDm04 + 06 improved peptide presentation and thus recruited also CTL with somewhat lower avidity.…”
Section: Nkg2d Expression and Target Cell Recognition By An Ie1-epitomentioning
confidence: 86%
“…Another striking finding revealed by the immunotherapy studies was the apparent irrelevance of the type of epitope; essentially all CTL lines (CTLL) protected in adoptive transfer assays regardless of the immunodominance status IgG1-iso of the respective antigenic peptide (for reviews, see [10] and the accompanying article by Holtappels et al in this issue of MMI). We therefore began to wonder if the observed protection was based on TCR-mediated recognition of MHC class-I presented antigenic peptide at all.…”
Section: In This Issue Of Mmi)mentioning
confidence: 99%
“…74,82 CMV infection elicits a broad CD8 1 T-cell response that is specific for an array of viral antigens. [90][91][92] However, in the brain, the MCMV-directed immune response seems to be quite focused. In newborn BALB/c mice, approximately 10% of brain-infiltrating CD8 1 T cells are directed to a single, immunodominant IE1 epitope at the peak of the response.…”
Section: Cells Effectively Inhibits Virus Replication But Does Not Nementioning
confidence: 99%
“…It has been reported that there are clonal expansions of certain T cell subgroups in the peripheral blood of CMV infectors in the acute phase (2). These T cells are considered as CMV-specific cytotoxic T lymphocytes (CTL), which play an important role in inhibiting CMV infection and reactivation (3).…”
Section: Introductionmentioning
confidence: 99%